ANALISIS TERHADAP UNDANG-UNDANG NOMOR 7 TAHUN 2017 TERKAIT DENGAN KETERWAKILAN PEREMPUAN DALAM LEMBAGA PENYELENGGARA PEMILU - Marwah Insan, Hakimah (Program Studi Hukum Tata Negara, 2024)
This research aims to explain the representation of women in election organizers such as the General Election Commission (KPU), the Election Supervisory Body (Bawaslu), and the Election Organizing Honorary Council (DKPP). This is a serious concern because women's political rights are essentially not only about the presence of women in political parties and parliament, but also in the entire process of holding elections, including election supervision. This research is library research or research using the library study method. In this research, it is explained that professional election management institutions are one of the determinants of the implementation of democratic elections. Open access and opportunities for women to become members of election organizers is one indicator that can be used to see whether the election organizer institution has been formed democratically. To realize equal access for women and men to be actively involved in public spaces is something that still requires special attention from stakeholders. One of the crucial problems related to this is that there is still an imbalance in the composition between men and women in organizing institutions.